Type 1, 2, and 1/2-Hybrid IncC Plasmids From China - Cheng, Qiaoxiang; Jiang, Xiaoyuan; Xu, Yanan; Hu, Lingfei; Luo, Wenbo; Yin, Zhe; Gao, Huixia; Yang, Wenhui; Yang, Huiying; Zhao, Yuee; Zhao, Xiaodong; Zhou, Dongsheng; et al. (Frontiers in Microbiology, 2019)
A collection of 11 IncC plasmids from China were fully sequenced herein and compared with reference plasmids pR148 and pR55. These 13 plasmids could be assigned into three different subgroups: type 1, type2, and type 1/2 hybrid. Type 1/2-hybrid plasmids are most likely emerged from homologous recombination between type 1 and type 2 plasmids. Different IncC plasmids had evolved to acquire quite different profiles of accessory modules and thus different collections of resistance genes. The accessory resistance modules including not only the blaCMY-carrying region, the ARI-A island and the ARI-B island, but also various additional kinds of resistance islands such as the blaCTX-M-carrying regions and the MDR regions. Insertion of accessory modules sometimes accompanied with deletion, inversion and translocation of surrounding backbone regions. pR148 and pR55 were confirmed to have the most complete backbones for type 1 and type 2, respectively. This was the first report of a blaIMP-8-carrying IncC plasmid, and that of three novel mobile elements: a Tn1696-derived unit transposon Tn6395, a class 2 integron In2-76, and an insertion sequence ISEcl10.